Iron Man 3 [compact disc] : heroes fall : music inspired by the motion picture. - Stockdale, Andrew; Williams, Robbie (Hollywood Records, 2013)
An album inspired by the upcoming Marvel Comics movie, Iron Man Three; Includes exclusive songs from today's compelling new and breakout artist.